International guidelines for the in vivo assessment of skin properties in non-clinical settings: part 1. pH - Stefaniak, Aleksandr B.; Plessis, Johan du; John, Swen M.; Eloff, Fritz; Agner, Tove; Chou, Tzu-Chieh; Nixon, Rosemary; Steiner, Markus F. C.; Kudla, Irena; Linn Holness, D. (Skin research and technology, 2013)
Background Skin surface pH is known to influence the dissolution and partitioning of chemicals and may influence exposures that lead to skin diseases. Non‐clinical environments (e.g. workplaces) are highly variable, thereby presenting unique measurement challenges that are not typically encountered in clinical settings. Hence, guidelines are needed for consistent measurement of skin surface pH in environments that are difficult to control. Methods An expert workshop was convened at the 5th International Conference on Occupational and Environmental Exposure of Skin to Chemicals to review available data on factors that could influence the determination of skin surface pH in non‐clinical settings with emphasis on the workplace as a worst case scenario. Results The key elements of the guidelines are: (i) minimize, to the extent feasible, the influences of relevant endogenous (anatomical position, skin health, time of day), exogenous (hand washing, barrier creams, soaps and detergents, occlusion), environmental (seasonality), and measurement (atmospheric conditions) factors; (ii) report pH measurements results as a difference or percent change (not absolute values) using a measure of central tendency and variability; and (iii) report notable deviations from these guidelines and other relevant factors that may influence measurements. Conclusion Guidelines on the measurement and reporting of skin surface pH in non‐clinical settings should promote consistency in data reporting, facilitate inter‐comparison of study results, and aid in understanding and preventing occupational skin diseases.